The problem of differentiation between types of measurement in Aristotle’s logic (the question of causes and mechanisms of transcendence - lasgaa, rabia (Journal of Social Sciences and Humanities, 2024)
The theory of analogy is considered the basic foundation of Aristotle’s logic, which was surrounded by many logical studies that investigated its nature as well as its rules, forms, and types of production. How can it be reduced to 19 times instead of 256 times, and how is it distributed among the four forms, even though the fourth form has raised many differences between those who deny it and those who defend it? These studies also addressed the importance of measurement, its benefits and disadvantages. The problem of differentiation was also raised in the Aristotelian theory of measurement when Aristotle and his followers distinguished between the four types of forms of convective measurement and even between the types of these forms Aristotle believed that the perfection of the first form lies in the certainty of its result, and that the deficiency of the remaining forms is its cause, not its certainty. Therefore, he saw that whenever we want to remove this uncertainty, we must reduce the types of these forms to a form of the first form in accordance with certain rules that regulate them.